Optimalisasi Limbah Sabut Kelapa Sebagai Media Tanam Hidpronik Di Desa Cinangka - Asep Rahmatullah; Eris Dwi Purnama; Regina Eka Anggraeni; Sekar Aulia Rahma; Fuad Febriyanto; Rizki Tri Rahmawan; Indra Cahyana (Universitas Maritim AMNI Semarang, 2023)
Cinangka Village is a village in the Cinangka District that has the greatest economic potential in the plantation sector, especially coconut production. The potential yield of coconut plants in Cinangka Village contributes to coconut production so that in 2021 Cinangka District can produce 1113.75 tonnes of coconut crops. The results of this coconut production are distributed to meet consumption needs in the tourism sector. The high consumption of coconut fruit has an impact on the high amount of coconut husk waste produced. The method for implementing these KKM-PkM activities uses participatory counseling methods, where this counseling is carried out by providing verbal and visual counseling. The results of KKM-PkM activities have had a positive impact, namely increasing public knowledge and awareness about the benefits of utilizing coconut husk waste into coconut husk powder (cocopeat) which is used as a planting medium using hydroponic techniques. Apart from that, if the utilization of coconut husk waste management is carried out on a massive scale supported by the use of coconut husk grinding machines, it can directly increase the income of the people of Cinangka Village.